2017
DOI: 10.1093/cercor/bhx337
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Identification of Thick, Thin, and Pale Stripes of Macaque Area V2 Using Submillimeter Resolution (f)MRI at 3 T

Abstract: Primate area V2 contains a repetitive pattern of thick, thin and pale cytochrome oxidase stripes that are characterized by largely discrete in- and output channels, as well as differences in function, and myelo- and cytoarchitecture. Stripes have been identified mainly using microscope-based imaging of tiny portions of superficially located V2, or by postmortem methods, hence, the quest for (quasi) noninvasive tools to study these mesoscale functional units. Only recently, stripe-like V2 patterns have been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 93 publications
4
31
0
Order By: Relevance
“…Sensitivity to horizontal binocular disparity is one important cue for visual depth (i.e., visual distance from the observer). Disparity-sensitive (stereoselective) activity has been reported in multiple visual areas, including V2, V3, V3A, and V4, in electrophysiological and imaging studies in nonhuman primates (Adams and Zeki, 2001;Hinkle and Connor, 2001;Thomas et al, 2002;Watanabe et al, 2002;Tsao et al, 2003;Chen et al, 2008;Anzai et al, 2011;Li et al, 2019) and in neuroimaging studies in humans (Tsao et al, 2003;Neri et al, 2004;Goncalves et al, 2015;Nasr et al, 2016;Nasr and Tootell, 2018). In a previous study, by taking advantage of high-field, high-resolution neuroimaging techniques, we found that clusters of such disparity-selective neurons show a strong selectivity for low-SF visual components (Tootell and Nasr, 2017).…”
Section: Why V3a?mentioning
confidence: 68%
“…Sensitivity to horizontal binocular disparity is one important cue for visual depth (i.e., visual distance from the observer). Disparity-sensitive (stereoselective) activity has been reported in multiple visual areas, including V2, V3, V3A, and V4, in electrophysiological and imaging studies in nonhuman primates (Adams and Zeki, 2001;Hinkle and Connor, 2001;Thomas et al, 2002;Watanabe et al, 2002;Tsao et al, 2003;Chen et al, 2008;Anzai et al, 2011;Li et al, 2019) and in neuroimaging studies in humans (Tsao et al, 2003;Neri et al, 2004;Goncalves et al, 2015;Nasr et al, 2016;Nasr and Tootell, 2018). In a previous study, by taking advantage of high-field, high-resolution neuroimaging techniques, we found that clusters of such disparity-selective neurons show a strong selectivity for low-SF visual components (Tootell and Nasr, 2017).…”
Section: Why V3a?mentioning
confidence: 68%
“…For M3, the template was one EPI image acquired during the separate field map scanning session. Finally, a slice-by-slice undistortion correction was performed according to the template EPI using a B-spline grid-based nonlinear registration method to reduce frame-to-frame distortions (Li et al, 2017).…”
Section: Surface Reconstructionmentioning
confidence: 99%
“…The same procedures as in our previous study (Li et al, 2017) were used to register each EPI template and the results in the same space to the reference anatomy of each subject. For M3, a distortion field was calculated based on the field map acquired in the same session as the EPI template and this was applied to the GLM results using FSL, thereby correcting for EPI distortions caused by magnetic field inhomogeneity.…”
Section: Epi Registration and Surface Projectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceivably, a similar pipeline can be constructed for anesthetized monkey data, although this will prove more challenging for awake nonhuman primate imaging data. Another major challenge may arise when high-resolution mesoscale data become available (Li et al, 2017). In certain instances, such data will be acquired from restricted parts of the brain, hampering their (automatic) registration with template brains.…”
mentioning
confidence: 99%